Understanding The Consequences of a City’s Spatial Structure through its Density Profile as Indicator. A Case Study in Manado Municipal, North Sulawesi, Indonesia - H.A. Rogi, Octavianus; O. Waani, Judy; Supardjo, Surijadi (Green Publisher Indonesia, 2024)
This paper aims to identify the spatial structure of Manado municipal, capital of North Sulawesi Province in Indonesia, through its density profile as indicator, which is the trend of density level according to the spatial units distance to the city center. This paper also tries to elaborate on the potential problems in the city as well as the urban planning policy which are associated with the spatial structure identified. The data used are the maps of administrative and built-up area and the distribution of population and service center by spatial units in Manado. The parameters of density profile examined are the administrative and built up density and the accessibility distance to the city center from the service center of the spatial units. By interpreting the existing density profile based on some relevant theoretical premises, the spatial structure type and its associative problems and policy can be identified. The result shows that the spatial structure of Manado municipal tends to be monocentric in certain boundary from the city center, but start shifting to polycentric pattern in the peri-urban zone. This characteristic is associated with some potential problems such as acute traffic congestion, air pollution, emerging of slum and squatter and the increased risk of disasters, specifically on downtown area. In the peri-urban zone, the potential significant problems is the phenomenon of sprawling and all its associated impacts such as fragmentation of green open space, increased dependence on private vehicles and increased investment and maintenance costs for infrastructure.